A case of multiple bilateral accessory nipples (polythelia) in a male - Bhatia, N; Bhatia, V (Journal of Institute of Medicine Nepal, 2000)
Polythelia is a condition in which accessory nipples are formed along the milk line. A 29 year old male was seen with multiple bilateral accessory nipples during routine abdominal examination. There were no other signs and symptoms of any other problem related to the presence of the accessory nipples.